Conditions and need of creation of Club of sports volunteering - Iryna Petrenko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the identification of prerequisites of creation of Club of sports volunteering. Material & Methods: 250 residents of Kharkiv participated in the research. The analysis of references and documents, poll (questioning), methods of mathematical data processing were used. Results: the social need for training of sport volunteers is defined on the basis of the data obtained as a result of the poll. The project of public organization «Club of sport volunteers» is developed. Conclusions: the results of the research demonstrate that there is need for creation of the permanent organization for training of sport volunteers today. The creation of public organization «Club of sports volunteering» will give the chance orderly and systematically to carry out training of sport volunteers thanks to the development and deployment of the permanent program of preparation, will promote the expansion of knowledge and experience of sports volunteer activity due to application and their fixing in practice, development and support of the sports volunteer movement.